WOMEN'S EXISTENCE IN CHRISTINA ROSSETTI'S 'BRIDE SONG' POEM (EKSISTENSI PEREMPUAN DALAM PUISI 'BRIDE SONG' KARYA CHRISTINA ROSSETTI) - Winarti Winarti (UIN Raden Mas Said Surakarta, 2018)
This article aims at describing women existence as reflected on Bride Song poem written by Christina Rossseti. Rossetti’s view on women’s lives was inspired much by her awareness toward the their conditions in Victorian’s era. In the meantime, women were shaped to be an individuals who fulfill the ideal standard as preferred by men. By Bride Song, Rosetti tried to break patriarchal domination toward women. She wanted to turn back the existence equivalence between men and women based on human rights. She also attemped to open the world’s perspective to accept women’s existence as important as men’s and not just a binary opposition of it. Women’s existence in Bride Song is not only a struggle against men’s domination in Victorian era, but it also has relevance with contemporary issues on women’s struggle to show their existence in this modern era.